Cultural Authority in the Age of Whitman: A Transatlantic Perspective - Leypoldt, Günter (Edinburgh University Press, 2022)
Frontmatter -- CONTENTS -- PREFACE -- ACKNOWLEDGMENTS -- INTRODUCTION: WHITMAN AND THE 'LAWLESS MUSIC' OF AMERICAN CULTURE -- Transnational Contexts of Nineteenth-Century US Discourse -- CHAPTER 1 THE NINETEENTH-CENTURY INTELLECTUAL FIELD -- CHAPTER 2 US DISCOURSE AND THE EXPRESSIVIST TURN -- Representative Authors -- CHAPTER 3 THE POET AS ORPHIC SINGER: RALPH WALDO EMERSON -- CHAPTER 4 WALT WHITMAN AND THE POETRY OF THE FUTURE -- Conceptual Fields of US Culture -- CHAPTER 5 THE MUSIC OF AMERICA -- Chapter 6 NATIONAL IDENTITY AND THE SMELL OF THE WOODS -- Chapter 7 THE DEMOCRATIC MUSE -- Inventing whitmanian authority -- Chapter 8 CONTEMPORARY RECEPTION -- Chapter 9 WHITMAN AMONG THE MODERNS -- EPILOG: AFTER THE AMERICAN RENAISSANCE -- BIBLIOGRAPHY -- INDEX